Mortality and Morbidity of Beef Calves in Free-Range Farms in Alentejo, Portugal—A Preliminary Study. (16th October 2019) - Santos, Rute; Cachapa, Ana; Carvalho, Graça P.; Silva, Carolina B.; Hernández, Laura; Costa, Lina; Pereira, Luísa S.; Minas, Miguel; Vala, Helena
Abstract : Extensive cow-calf beef cattle farms play a significant role in Portuguese livestock production, but records of important production variables, such as calf mortality, are scarce. To assess herd-level calf mortality and its potential economic impact, farmers from the Alentejo region were asked to fill a questionnaire regarding herd size, feeding and reproductive management practices, calf mortality (from birth to weaning), and detection of the main morbidity causes, as well as of sudden, unexplained deaths during the previous 12 months. Farmers were also requested to quantitatively assess the economic impact of calf mortality on their annual revenue. In the majority of farms, the herd size was larger than 100 animals. The median stocking rate was 0.41 adult animals/hectare, and 70% of farmers stated their farm was self-sufficient in forage. The percent of live births that resulted in weaned calves averaged 94.3%, which led to the assumption of a 5.7% calf mortality rate from birth to weaning. In the previous 12 months, 78.8% of the farms identified at least one case of calf diarrhea, 60.7% identified at least one case of respiratory disease, and 82.1% had at least one sudden, unexplained calf death. As expected, farmers that assessed a higher impact of calf losses on their annual economic revenue were also those who reported higher incidences of calf diarrhea, respiratory disease, and sudden, unexplained deaths. One-quarter of the farmers were unable to assess the economic impact of calf mortality on the farm's revenue. Herd size appears to have a predictive value on calf mortality in the first month of life, and from 30 days to weaning. The number of sudden, unexplained calf deaths seems to have a predictive value on overall calf mortality (from birth to weaning), suggesting that the farms' management practices probably play an important role in calf mortality throughout the suckling period. Further studies are needed to fully understand calf mortality in Portuguese extensive rearing systems.